Parental Stress in Supporting Online Learning of Elementary School Children During the COVID-19 Pandemic: A Cross-Sectional Study - Putri Rejeki Mawarni; Siti Khadijah; Dwi Ariani Sulistyowati (Poltekkes Kemenkes Surakarta, 2023)
Background: The implementation of online primary school level learning during the covid 19 pandemic has caused stress levels for parents. This is related to the process of assisting online learning there are obstacles or burdens experienced by parents. The study analysed the relationship between online learning assistance and stress levels of parents of elementary school children in grades 1-4 during the Covid 19 pandemic. Methods: Quantitative research design with a cross-sectional approach. The study was conducted on 52 students using random sampling techniques. Data analysis using Kendall's tau-b test. Results: Statistical tests showed there was a significant relationship between online learning assistance and stress level (p value <0.001). The strength of the relationship is in the strong category (r = 0.653) with predominantly moderate online learning assistance (67.3%) and moderate stress level (63.5%). Conclusion: There is a significant relationship between online learning assistance and stress level. The study underscores the importance of structured support programs to help parents manage stress during elementary online learning, emphasizing digital literacy, time management, and emotional support to enhance parental involvement.